The Theoretical Evaluation of Saccharin Electrochemical Detection on CP-Based Diazonium Salts - Романів, Людмила Вікторівна (ANALYTICAL & BIOANALYTICAL ELECTROCHEMISTRY, 2016)
- detection, based on its azo-coupling with conducting polymer-based diazonium salts has been evaluated theoretically. The mathematical model, describing the case, was developed and analyzed by means of linear stability theory and bifurcation analysis. It was shown, that the reaction may be realized with electroanalytical efficiency, when the pH is neutral or mildly acidic. Also it was shown, that the oscillatory behavior in this case is more probable, than for general case, due to DEL influences of diazocoupling.
Keywords: Saccharine, Electrochemical detection, Azo coupling conducting polymers, Stable steady-state